One Health: a concept led by Africa, with global benefits. (9th May 2015) - Kamani, Titus Mlengeya; Kazwala, Rudovick; Mfinanga, Sayoki; Haydon, Dan; Keyyu, Julius; Lankester, Felix; Buza, Joram
Abstract : Titus Mlengeya Kamani and others argue that Africa is well positioned and equipped to conduct and benefit from an integrated approach